The prognostic effect of sixteen malnutrition/inflammation-based indicators on the overall survival of chemotherapy patients - Liu, Tong; Liu, Chenan; Deng, Li; Song, Mengmeng; Lin, Shiqi; Shi, Hanping (Frontiers in Immunology, 2023)
Background: Studies have confirmed the validity of malnutrition/inflammation-based indicators among cancer patients compared to chemotherapy patients. Moreover, it is necessary to identify which indicator is the best prognostic predictor for chemotherapy patients. This study attempted to determine the best nutrition/inflammation-based indicator of overall survival (OS) for chemotherapy patients. Methods: In this prospective cohort study, we collected 16 nutrition/inflammation-based indicators among 3,833 chemotherapy patients. The maximally selected rank statistics were used to calculate the optimal values of cutoffs for continuous indicators. OS was evaluated using the Kaplan–Meier method. The associations of 16 indicators with survival were evaluated using Cox proportional hazard models. The predictive ability of 16 indicators was assessed via time-dependent receiver operating characteristic curves (time-ROC) and the C-index. Results: All indicators were significantly associated with worse OS of chemotherapy patients in the multivariate analyses (all P < 0.05). Time-AUC and C-index analyses indicated that the lymphocyte-to-CRP (LCR) ratio (C-index: 0.658) had the best predictive ability for OS in chemotherapy patients. The tumor stage significantly modified the association between inflammatory status and worse survival outcomes (P for interaction < 0.05). Compared to patients with high LCR and I/II tumor stages, patients with low LCR and III/IV tumor stages had a 6-fold higher risk of death. Conclusions: The LCR has the best predictive value in chemotherapy patients compared with other nutrition/inflammation-based indicators.